The Impact of English Teachers’ Professional Competence on Students’ Performances of the Second Grade at SMA Swasta Santu Xaverius Gunungsitoli in 2023/2024 - Laoli, Markus Cames; Zebua, Elwin Piarawan; Zega, Riswan; Telaumbanua, Yasminar Amaerita (Tuhenori: Jurnal Ilmiah Multidisiplin, 2024)
This study aimed to explore the impact of English teachers' professional competence on the performance of second-grade students at SMA Swasta Santu Xaverius Gunungsitoli. Employing a quantitative research approach, the study utilized a correlational design to identify patterns between teacher professional competence and student performance. Data were collected through questionnaires and analyzed using simple linear regression. The findings revealed a moderate positive correlation between teacher professional competence and student performance, indicating that higher teacher competence levels significantly enhance student academic outcomes. Consequently, the null hypothesis was rejected, and the alternative hypothesis was accepted. These results underscore the importance of continuous professional development for teachers to improve student performance